Prognostic Value of the Systemic Immune-Inflammation Index in EGFR Mutation-Positive Lung Adenocarcinoma Patients Treated with Tyrosine Kinase Inhibitors - Marsheilla Riska; Haryati Haryati; Eko Suhartono; Tenri Ashari Wanahari (Faculty of Medicine Universitas Airlangga, 2022)
Introduction: Inflammatory parameters calculated from complete blood counts such as neutrophil to lymphocyte ratio (NLR), platelet to lymphocyte ratio (PLR), and systemic immune-inflammatory index (SII) are related to poor prognosis in lung cancer patients. This study aimed to explore a correlation between NLR, PLR, and SII to survival rates in advanced lung adenocarcinoma with tyrosine kinase inhibitors (TKIs) as the main treatment choice. Methods: This was a retrospective observational study of patients with epidermal growth factor receptor (EGFR) mutation-positive lung adenocarcinoma treated by TKIs at Ulin General Hospital Banjarmasin from January 2017 to December 2019. The optimal cut-off values for NLR, PLR, and SII were obtained using the receiver operating characteristic curve (ROC). Kaplan–Meier analyses were used to assess the prognostic value of inflammation parameters in overall survival (OS) and progression-free survival (PFS). Results: This study involved 50 samples, 62% male, with an average age of 55.98 years old, 94% in stage IVA, EGFE mutation in exon 19 (58%) and exon 21 (42%). About 58% of patients have a smoking history. The optimal cut-off value for NLR, PLR, and SII was 6.095, 356.935, and 1767.0, respectively. However, only the SII was significantly associated with survival; SII ≥ 1767.0 correlated with shorter OS (18 months vs. 28 months, p = 0.014) and PFS (7 months vs. 12 months, p = 0.004). Conclusion: Pre-treatment SII can be a prognostic factor for survival in EGFR mutation-positive lung adenocarcinoma patients receiving TKIs.